An exploratory study of the associations between maternal iron status in pregnancy and childhood wheeze and atopy. Issue 12 (28th December 2014) - Nwaru, Bright I.; Hayes, Helen; Gambling, Lorraine; Craig, Leone C. A.; Allan, Keith; Prabhu, Nanda; Turner, Steven W.; McNeill, Geraldine; Erkkola, Maijaliisa; Seaton, Anthony; McArdle, Harry J.; Devereux, Graham
<x content-type="archive" xml:space="preserve">Abstract</x> Maternal nutritional status during pregnancy has been reported to be associated with childhood asthma and atopic disease. The Avon Longitudinal Study of Parents and Children has reported associations between reduced umbilical cord Fe status and childhood wheeze and eczema; however, follow-up was short and lung function was not measured. In the present study, the associations between maternal Fe status during pregnancy and childhood outcomes in the first 10 years of life were investigated in a subgroup of 157 mother–child pairs from a birth cohort with complete maternal, fetal ultrasound, blood and child follow-up data. Maternal Fe intake was assessed using FFQ at 32 weeks of gestation and Hb concentrations and serum Fe status (ferritin, soluble transferrin receptor and TfR-F (transferrin receptor:ferritin) index) were measured at 11 weeks of gestation and at delivery. Maternal Fe intake, Hb concentrations and serum Fe status were found to be not associated with fetal or birth measurements. Unit increases in first-trimester maternal serum TfR concentrations (OR 1·44, 95 % CI 1·05, 1·99) and TfR-F index (OR 1·42, 95 % CI 1·10, 1·82) (i.e. decreasing Fe status) were found to be associated with an increased risk of wheeze, while unit increases in serum ferritin concentrations (i.e. increasing Fe status) were found to be associated with increases in standardised mean peak expiratory flow (PEF) (β 0·25, 95 % CI 0·09, 0·42) and forced expiratory volume in the first second (FEV1) (β 0·20, 95 % CI 0·08, 0·32) up to 10 years of age. Increasing maternal serum TfR-F index at delivery was found to be associated with an increased risk of atopic sensitisation (OR 1·35, 95 % CI 1·02, 1·79). The results of the present study suggest that reduced maternal Fe status during pregnancy is adversely associated with childhood wheeze, lung function and atopic sensitisation, justifying further studies on maternal Fe status and childhood asthma and atopic disease.